2010
DOI: 10.1007/s00737-010-0147-5
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with pregnancy loss aftercare: are women getting what they want?

Abstract: While there is increasing recognition that early miscarriage represents a significant loss experience that often provokes depression and anxiety, women's dissatisfaction with some aspects of care received from healthcare professionals following a pregnancy loss and the potentially negative consequences of this are often less recognized. This review examines available literature to identify what comprises "treatment as usual," how satisfied women are with the typical services they receive from healthcare person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0
5

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 28 publications
2
51
0
5
Order By: Relevance
“…As a result of this it would seem that women who miscarry are experiencing higher levels of depression and anxiety than women without a recent reproductive loss (Geller, Psaros, & Kornfield, 2010).…”
Section: Chapter One: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…As a result of this it would seem that women who miscarry are experiencing higher levels of depression and anxiety than women without a recent reproductive loss (Geller, Psaros, & Kornfield, 2010).…”
Section: Chapter One: Introductionmentioning
confidence: 97%
“…Swanson (1999b) found that 39% of women grieved for six months or longer after the loss. Elevated levels of anxiety were found in 32% of women 12 weeks after miscarriage (Geller, Psaros, & Kornfield, 2010) and these rates can be as high as 45% of women, persisting for up to a year (Nikcevic & Nicolaides, 2013;Sejourne, Callahan, Chabrol, 2010b). Compared to their male counterparts, women appear quite vulnerable to developing a depressive episode following a stressful life event (Groh & Hoes, 2003) and as many as 15% of women will experience depression for up to a year after a miscarriage (Nikcevic & Nicolaides, 2013 Research shows that nurse practitioners provide treatment for women with depression that is consistent with national standards (Groh & Hoes, 2003).…”
Section: Chapter One: Introductionmentioning
confidence: 99%
See 3 more Smart Citations